Akulturasi Masjid Agung Nur Sulaiman Banyumas dalam Pembelajaran Sejarah Lokal di SMA Negeri 1 Baturraden - Rahayu, Suci (Keraton: Journal of History Education and Culture, 2021)
History subjects are one of a number of subjects studied at the elementary to high school level.  History Subjects have an important role in the life of the nation and the country. In the concept of historical learning, those objectives are more realized specifically such as historical awareness, nationalism, patriotism, humanoria insights in addition to academic proficiency that until now has not been intensively socialized so that the main substance of the curriculum is less than achieved the target. To realize it all is absolutely necessary efforts to improve the quality of historical learning in particular and national education in general. History subjects play an important role in the formation of the character of learners, where the general goal of historical learning is to develop an understanding of the self; provide a precise picture of the concepts of time, space and society, make the community able to evaluate the values of the results that have been achieved by its generation, teach tolerance, instill, intellectual attitudes, expand the horizons of intellectuality, teach moral principles, instill orientation into the future, provide mental training, train learners to deal with controversial issues, help find a way out for various social problems and perse orangan, strengthening the sense of nationalism; develop international understanding, and develop useful skills.